Pharmacothera-peutic activity Lomatogonium Carinthiacum extract at experimental hepatitis - A. V. Fedorov; S. M. Nikolaev; Z. G. Sambuyeva; Ya. G. Razuvaeva; A. A. Toropova; E. V. Ferubko (Acta Biomedica Scientifica)
Pharmacotherapeutic efficiency of the dry extract from Lomatogonium carinthiacum in toxic hepatitis was studied. Experimental hepatitis was caused by the introduction of tetracycline hydrochloride to Wistar white rats in the dose of 1,0 g/kg of the animal weight once a day during 7 days. The extract from L. carinthiacum was administered per os in the dose of 100 mg/kg during 26 days. It was established that the extract from L. carinthiacum had a marked hepatoprotective effect in the case of tetracycline hepatitis in white rats that is characterized by inhibition of the disturbances in choleretic and cholate-synthetic functions of the liver: the increase of bile secretion rate, preservation of cholate concentration in the bile, the decrease in the content of cholesterol triacylglycerides and alkaline phosphatase activity in the animal blood serum during the whole period of experiments. The tested remedy diminishes dystrophic and necrotic processes in hepatocytes, decreases the intensity of inflammatory infiltration in the liver and stimulates regeneration of liver cells in tetracycline hepatitis. The decrease of MDA content in the liver homogenate and increase in catalase activity against the same indices in control animals testify the marked antioxidant effect of L. carinthiacum.